Round-Robin Study for Ice Adhesion Tests - Nadine Rehfeld; Jean-Denis Brassard; Masafumi Yamazaki; Hirotaka Sakaue; Marcella Balordi; Heli Koivuluoto; Julio Mora; Jianying He; Marie-Laure Pervier; Ali Dolatabadi; Emily Asenath-Smith; Mikael Järn; et al. (Aerospace, 2024)
Ice adhesion tests are widely used to assess the performance of potential icephobic surfaces and coatings. A great variety of test designs have been developed and used over the past decades due to the lack of formal standards for these types of tests. In many cases, the aim of the research was not only to determine ice adhesion values, but also to understand the key surface properties correlated to low ice adhesion surfaces. Data from different measurement techniques had low correspondence between the results: Values varied by orders of magnitude and showed different relative relationships to one another. This study sought to provide a broad comparison of ice adhesion testing approaches by conducting different ice adhesion tests with identical test surfaces. A total of 15 test facilities participated in this round-robin study, and the results of 13 partners are summarized in this paper. For the test series, ice types (impact and static) as well as test parameters were harmonized to minimize the deviations between the test setups. Our findings are presented in this paper, and the ice- and test-specific results are discussed. This study can improve our understanding of test results and support the standardization process for ice adhesion strength measurements.